2015
DOI: 10.1007/s12020-015-0832-2
|View full text |Cite
|
Sign up to set email alerts
|

Impaired immune regulation after radioiodine therapy for Graves’ disease and the protective effect of Methimazole

Abstract: Both therapies for Graves' disease (GD), radioactive iodine (RAI) and antithyroid drugs (ATD), were reported to have specific immune effects. We aimed at investigating the effects of RAI therapy on cellular subsets involved in immune regulation. We conducted a thirty day follow-up prospective cohort study of adult patients. Patients eligible for RAI therapy at our centre were approached. Twenty seven patients with GD were recruited, among whom 11 were treated with ATD. Twenty-two healthy subjects (HS) were als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
0
7
0
2
Order By: Relevance
“…This phenomenon has been explained by the release of preformed thyroid hormones and autoantibodies into the bloodstream following RAI-mediated destruction of the thyroid gland 1. It has also been associated with increased levels of peripheral blood lymphocytes (CD3+, CD4+ and CD3+ HLA-DR+), which are instrumental in the pathogenesis of SSc 16. However, the absence of active eye disease in our patient plus the complete resolution of her hyperthyroid state after RAI both make this theory less likely.…”
Section: Discussionmentioning
confidence: 69%
“…This phenomenon has been explained by the release of preformed thyroid hormones and autoantibodies into the bloodstream following RAI-mediated destruction of the thyroid gland 1. It has also been associated with increased levels of peripheral blood lymphocytes (CD3+, CD4+ and CD3+ HLA-DR+), which are instrumental in the pathogenesis of SSc 16. However, the absence of active eye disease in our patient plus the complete resolution of her hyperthyroid state after RAI both make this theory less likely.…”
Section: Discussionmentioning
confidence: 69%
“…Radioiodine treatment in patients with Graves disease can enhance the autoimmune response and lead to a higher TRAb concentration 16 . Another factor underlying the increased autoimmune response is a disturbance in the number and suppressive function of natural killer cells and conventional T cells 17 . A statistically significant increase in the PSV in both the CRA and OA in both patient groups is thus related to an abrupt change in the hormonal status after radioiodine therapy and is derived from intensified peripheral hyperkinetic circulation dependent on cardiac muscle performance 18 …”
Section: Discussionmentioning
confidence: 99%
“…16 Another factor underlying the increased autoimmune response is a disturbance in the number and suppressive function of natural killer cells and conventional T cells. 17 A statistically significant increase in the PSV in both the CRA and OA in both patient groups is thus related to an abrupt change in the hormonal status after radioiodine therapy and is derived from intensified peripheral hyperkinetic circulation dependent on cardiac muscle performance. 18 In both groups, there were no statistically significant differences in RI values (in both the CRA and OA) across 3 consecutive measurements (before iodine treatment and 2 weeks and 4 weeks after radioiodine administration).…”
Section: Comparisons Between Groupsmentioning
confidence: 93%
“…Hyperthyroidism is the most common organ-specific autoimmune disease and the most important reason for Graves' ophthalmopathy ( 13 – 15 ). Although the pathogenesis of hyperthyroidism has not been completely elucidated, recent studies indicated that the change of immunologic function may be closely correlated with the occurrence of hyperthyroidism ( 16 , 17 ). The maintenance of immune function is closely associated with immunosuppressive cells existing in the body.…”
Section: Discussionmentioning
confidence: 99%